1993
DOI: 10.1111/j.1471-0528.1993.tb15217.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular autonomic reflexes in mid‐pregnancy

Abstract: Objective To study the physiological responses to noninvasive cardiovascular autonomic function tests in normal pregnancy. Design Cardiovascular autonomic responses in 60 women at 22 to 29 weeks gestation and 62 nonpregnant women were investigated using the Valsalva manoeuvre as well as orthostatic, quiet breathing, deep breathing, and isometric handgrip tests. Results Compared with nonpregnant women, those who were pregnant showed significantly lower heart rate variability during normal brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
22
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 27 publications
6
22
0
Order By: Relevance
“…[9] In our study, the maximum rise in DBP during isometric handgrip exercise was significantly less in the second trimester when compared to controls. This is in accordance with many studies [4,8,[10][11][12] which have shown that there is decreased sympathetic activity more in the second trimester, which explains the decreased peripheral vascular resistance in the second trimester is by decreased sympathetic activity. [8] The reduced BP response reported could be due to an antagonistic effect of products of uteroplacental unit such as progesterone or a diminished contractile response of the blood vessels to adrenaline.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…[9] In our study, the maximum rise in DBP during isometric handgrip exercise was significantly less in the second trimester when compared to controls. This is in accordance with many studies [4,8,[10][11][12] which have shown that there is decreased sympathetic activity more in the second trimester, which explains the decreased peripheral vascular resistance in the second trimester is by decreased sympathetic activity. [8] The reduced BP response reported could be due to an antagonistic effect of products of uteroplacental unit such as progesterone or a diminished contractile response of the blood vessels to adrenaline.…”
Section: Discussionsupporting
confidence: 80%
“…[17] In our study of HR response to deep breathing, the ratio of maximum-to-minimum RR-interval during respiratory cycles, that is, the E/I ratio of RR intervals, was found to be significantly less in the second trimester compared to controls. In accordance with our results, many studies [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] showed HR response to deep breathing expressed as deep breathing difference (DBD), a measure of cardiac parasympathetic function was observed to be significantly lower in pregnant women when compared to control group and generally followed a decreasing trend with increase in gestation. [4] This finding was in conformity with observation of Ekholm et al who suggested a multifactorial basis for it.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…RSA is substantially reduced during rapid compared to slow breathing (Brown et al, 1993;Grossman et al, 1991). This effect may also be present during pregnancy as high frequency heart rate variability (HRV) is reduced in the second (Ekholm et al, 1993) and third trimester of pregnancy (Eneroth-Grimfors et al, 1994). There is debate, however, as to whether reduced HRV in pregnancy is due to changes in lung volumes or other physiologic changes associated with pregnancy (Ekholm and Erkkola, 1996).…”
Section: Rsa and Body Habitusmentioning
confidence: 99%
“…[3,9] Ekholm et al studies on cardiac autonomic function in human pregnancy have produced conflicting results. Their fi ndings of reduced total power [10,11] and attenuated HR responses to orthostatic tests and the Valsalva maneuver [11] suggest that cardiac parasympathetic modulation is reduced in the resting state during mid pregnancy (22-29 wk of gestation). Studies conducted in early to mid gestation (11-27 wk) [12] were reported reduction in low-frequency HRV during the day and reduction in high-frequency HRV at night.…”
Section: Introductionmentioning
confidence: 99%